2014
DOI: 10.1039/c3np70054b
|View full text |Cite
|
Sign up to set email alerts
|

The phosphopantetheinyl transferases: catalysis of a post-translational modification crucial for life

Abstract: Although holo-acyl carrier protein synthase, AcpS, a phosphopantetheinyl transferase (PPTase), was characterized in the 1960s, it was not until the publication of the landmark paper by Lambalot et al. in 1996 that PPTases garnered wide-spread attention being classified as a distinct enzyme superfamily. In the past two decades an increasing number of papers has been published on PPTases ranging from identification, characterization, structure determination, mutagenesis, inhibition, and engineering in synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
387
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 311 publications
(395 citation statements)
references
References 374 publications
(740 reference statements)
4
387
1
3
Order By: Relevance
“…A prerequisite for the synthesis of all NRPs, PKs, and PK-NRP hybrids is the posttranslational attachment of P-Pant arms from coenzyme A (CoA) to a conserved serine residue of a carrier protein, converting inactive apo-synthases to active holo-synthases. This reaction is catalyzed by members of the type II family of phosphopantetheinyl transferases (PPTases) (12). The core genome of Escherichia coli codes for two type II PPTases, i.e., EntD and YieE (ECK3705, b3712, JW3690) (13).…”
mentioning
confidence: 99%
“…A prerequisite for the synthesis of all NRPs, PKs, and PK-NRP hybrids is the posttranslational attachment of P-Pant arms from coenzyme A (CoA) to a conserved serine residue of a carrier protein, converting inactive apo-synthases to active holo-synthases. This reaction is catalyzed by members of the type II family of phosphopantetheinyl transferases (PPTases) (12). The core genome of Escherichia coli codes for two type II PPTases, i.e., EntD and YieE (ECK3705, b3712, JW3690) (13).…”
mentioning
confidence: 99%
“…It proved that mutation of zmsO will not affect the transcriptional levels of polyketide synthase ZmsA (Zhou et al 2011) and non-ribosomal peptide synthase ZmsK (Cheng et al 2013) in D. zeae. Analysis of the amino acid sequence of ZmsO showed that it is a 4′-phosphopantetheinyl transferase, which usually transform 4′-phosphopantetheine moiety from CoA to apo-CPs to form holo-CPs (Beld et al 2014;Sunbul et al 2009). Previous studies have classified the 4′-phosphopantetheinyl transferases into three types (Beld et al 2014) (Fig.…”
Section: Ec1mentioning
confidence: 99%
“…Analysis of the amino acid sequence of ZmsO showed that it is a 4′-phosphopantetheinyl transferase, which usually transform 4′-phosphopantetheine moiety from CoA to apo-CPs to form holo-CPs (Beld et al 2014;Sunbul et al 2009). Previous studies have classified the 4′-phosphopantetheinyl transferases into three types (Beld et al 2014) (Fig. 5a).…”
Section: Ec1mentioning
confidence: 99%
See 1 more Smart Citation
“…There are three 4′-phosphopantetheine transferases encoded in the S. nodosus genome. These were assigned functions based on size, conserved motifs, and homology to known phosphopantetheinyltransferases (Beld et al, 2014) One, SNOD_19940 protein, is likely to be involved in modifying discrete ACPs involved in fatty acid biosynthesis. Another, SNOD_28340 protein, is likely to be involved in modifying ACP domains in NRPSs and PKSs.…”
Section: Phosphopantetheine Transferasesmentioning
confidence: 99%